Long way to diagnosis – case report of 23-year old patient with multifocal abdominal endometriosis - Gacoń, Ewa; Zembala, Julita; Kucharski, Jakub; Ząber, Aldona; Zapała, Brygida (Journal of Education, Health and Sport, 2023)
Endometriosis is a chronic gynaecological disease characterized by the presence of the uterine mucosa that functions in accordance with the menstrual cycle outside of its usual location. This disease significantly reduces the quality of life of women facing numerous ailments, most often pain, and may lead to reduced fertility. The prevalence of endometriosis is difficult to determine due to the complexity and lengthy diagnosis. It is estimated that this disease occurs in 3-8% of women of reproductive age, and symptoms may also appear after menopause. It is worth noting that the relationship between the disease’s severity and endometriosis symptoms is often not proportional. The aim of the paper is to present a case report of a 23-year-old female patient with endometriosis, to differentiate the disease from irritable bowel syndrome and to draw attention to the problematic and lengthy diagnostic process due to the multitude of symptoms from various organs. Material and method: Study of an individual case of a patient and a review of scientific articles available in Google Scholar and a review of publicly available textbooks in the field of medicine. The paper emphasizes the need to broaden the knowledge about endometriosis by specialists in many fields of medicine and points to the lack of quick, minimally invasive tests enabling efficient diagnosis of the disease. Increasing the awareness of doctors including other specializations than gynaecology, organizing campaigns to increase awareness of the disease among women, which may contribute to earlier diagnosis of patients, earlier application of an effective treatment, and improvement of patients’ quality of life.